Improving the operation of a drum grain dryer with justification of the low-temperature mode parameters - Pazyuk, Vаdym; Dub, V.; Tereshkin, O.; Zahorulko, Andrii; Lebedynets, Iryna; Pankov, Dmitry; Hotvianska, A. (My University, 2020)
The proposed engineering and tech-nological solutions are aimed at improv-ing the operation of a low-temperature drum grain dryer by using a combined mechanical vibration exciter, with the further justification of low-temperature regime parameters. Запропоновані інженерно-технологічні рішення спрямовані на покращення роботи низькотемпературної барабанної зерносушарки шляхом використання комбінованого механічного віброзбудника з подальшим обґрунтуванням параметрів низькотемпературного режиму.
Keywords: low-temperature drying; низькотемпературне сушіння; барабанна зерносушарка; drum grain dryer; сушіння зерна; grain drying; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка